81.4k views
0 votes
Which trinomial is the product of the expression below? (3x+2)(2x-3)

A. 6x^2-13x-6

B. 6x^2+5x-6

C. 6x^2-5x-6

D. 6x^2+13x-6

User Davka
by
5.6k points

1 Answer

1 vote

Answer:

C

Explanation:

Expand the factors to obtain the product.

Each term in the second factor is multiplied by each term in the first factor

(3x + 2)(2x - 3)

= 3x(2x - 3) + 2(2x - 3) ← distribute both parenthesis

= 6x² - 9x + 4x - 6 ← collect like terms

= 6x² - 5x - 6 → C

User Loosecannon
by
5.0k points